Seasonal Changes in the Plant Growth-Inhibitory Effects of Rosemary Leaves on Lettuce Seedlings - Appiah, K.S.; Omari, R.A.; Onwona-Agyeman, S.; Amoatey, C.A.; Ofosu-Anim, J.; Smaoui, A.; Arfa, A.B.; Suzuki, Y.; Oikawa, Y.; Okazaki, S.; Katsura, K.; Isoda, H.; et al. (Plants, 2022)
Plant biodiversity has been studied to explore allelopathic species for the sustainable management of weeds to reduce the reliance on synthetic herbicides. Rosemary (Rosmarinus officinalis L., syn Salvia rosmarinus Spenn.), was found to have plant growth-inhibitory effects, and carnosic acid was reported as an allelochemical in the plant. In this study, the effects of seasonal variation (2011–2012) on the carnosic acid concentration and phytotoxicity of rosemary leaves from two locations in Tunisia (Fahs and Matmata) were investigated. The carnosic acid concentration in rosemary leaves was determined by HPLC, and lettuce (Lactuca sativa L.) was used as the receptor plant in the phytotoxicity bioassay. The highest carnosic acid concentration was found in rosemary samples collected in June 2011, which also had the highest inhibitory activity. Furthermore, a significant inverse correlation (r = 0.529; p < 0.01) was found between the inhibitory activity on lettuce hypocotyl and the carnosic acid concentration in rosemary leaves. Both temperature and elevation had a significant positive correlation with carnosic acid concentration, while rainfall showed a negative correlation. The results showed that the inhibitory effects of rosemary leaf samples collected in summer was highest due to their high carnosic acid concentration. The phytotoxicity of rosemary needs to be studied over time to determine if it varies by season under field conditions.
Research Article
Keywords: Mediterranean climate; elongation; allelochemicals; specific activity; phytotoxicity